How do you verify ##(1+cosx)/(1-cosx) – (1-cosx)/(1+cosx)=4cotxcscx##?

Verify trig expression.

Develop left side numerator:
##(1 + cos x)^2 – (1 – cos x)^2 = 4cos x##
Develop left side denominator:
##(1 – cos x)(1 + cos x) = (1 – cos^2 x) = sin^2 x.##
Full left side:
##(4cos x)/sin^2 x = 4(cos x/sin x) (1/sin x) = 4cot x.csc x##

Posted in Uncategorized

Leave a Reply

Your email address will not be published. Required fields are marked *

You may use these HTML tags and attributes:

<a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>